Back contact cell with specific reduced lamination layer and preparation and application thereof
By using a specific anti-reverse composite layer of silicon nitride and carbon-doped silicon oxide in the back contact battery, the problems of poor anti-reverse effect and low short-circuit current in the prior art are solved, a more stable film layer and higher production yield are achieved, and the overall efficiency of the battery is improved.
Patent Information
- Application Number
- CN202510345104.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-24
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2045-03-24
AI Technical Summary
The existing back contact batteries have poor anti-reverse effects and low short-circuit current, and low production yield. This is mainly due to the poor solution corrosion resistance of nitrogen-rich silicon nitride films, which leads to large fluctuations in the film thickness, affecting battery efficiency.
A specific anti-reverse composite layer is adopted, including silicon nitride and carbon doped silicon oxide sequentially on the outer surface of the passivation layer. The corrosion rate of carbon doped silicon oxide is below 1.5 Å/s, a thickness of 60-150 nm, and the thickness ratio of silicon nitride to carbon doped silicon oxide is 1: (0.5-2), to improve the stability and production yield of the film layer.
By using a specific anti-reverse composite layer, the stability and production yield of the film layer are improved, the short-circuit current is enhanced, and the overall efficiency of the battery is improved.
Smart Images

Figure CN119866109A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of back contact batteries, and in particular relates to a back contact battery with a specific anti-reflection composite layer and a preparation method and application thereof. Background Art
[0002] The current back-contact battery process with relatively low equipment cost is as follows: S101, providing a silicon wafer with a single-sided textured and single-sided polished structure; S102, sequentially coating the first semiconductor layer and the first mask layer on the back of the silicon wafer; S103, laser or etching an opening on the back of the silicon wafer, removing the first mask layer and part of the first semiconductor layer, and forming a second semiconductor opening area; S104, cleaning the silicon wafer, and removing the first semiconductor layer in the second semiconductor opening area; S105, forming a third semiconductor layer on the front side, the third semiconductor layer comprising a front passivation layer and an anti-reflection layer, the front passivation layer comprising an intrinsic amorphous silicon layer and an N-type doped non- A crystalline or microcrystalline silicon layer, wherein the anti-reflection layer is at least one of silicon nitride, silicon oxynitride, and silicon oxide; S106, removing the back-surface coating, and cleaning to further purify the second semiconductor opening area; S107, forming a second semiconductor layer on the back of the silicon wafer; S108, laser or etching openings on the back of the silicon wafer to form first semiconductor regions alternately arranged with the second semiconductor regions; S109, depositing a conductive film on the back of the silicon wafer; S110, forming an isolation groove between the first semiconductor region and the second semiconductor region by laser or etching; S111, forming metal electrodes on the first semiconductor region and the second semiconductor region of the silicon wafer.
[0003] However, in the existing back-contact battery, after the passivation layer and the anti-reflection layer are formed on the front side, there will be a certain amount of plating layer on the back side, which needs to be removed by wet chemical cleaning. In order to ensure a good anti-reflection effect, the existing anti-reflection layer generally uses at least a nitrogen-rich silicon nitride film layer (nitrogen-rich means that the nitrogen content is relatively high, and the refractive index of nitrogen-rich silicon nitride is generally below 1.98). The nitrogen-rich silicon nitride film layer generally has poor resistance to solution corrosion. When the concentration of the solution fluctuates due to factors such as liquid replenishment or temperature, the film thickness of the anti-reflection layer will fluctuate greatly, the anti-reflection effect will be greatly reduced, the short-circuit current density of the battery will be greatly affected, and the production yield will be low.
[0004] It should be noted that this part of the present invention only provides background technology related to the present invention and does not necessarily constitute prior art or known technology. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art that the back-contact battery has poor anti-reflection effect, low short-circuit current and low production yield, and to provide a back-contact battery with a specific anti-reflection composite layer and its preparation and application, which is beneficial to taking into account the optical effect while improving the stability of the film layer and the production yield, increasing the short-circuit current and improving the battery efficiency.
[0006] In order to achieve the above-mentioned purpose, in a first aspect, the present invention provides a back-contact battery with a specific anti-reflection composite layer, comprising a silicon wafer, a first semiconductor layer and a second semiconductor layer alternately arranged on the back side of the silicon wafer, a passivation layer and an anti-reflection composite layer sequentially arranged on the front side of the silicon wafer, the anti-reflection composite layer comprising silicon nitride and carbon-doped silicon oxide sequentially arranged on the outer surface of the passivation layer, the corrosion rate of the carbon-doped silicon oxide in a hydrofluoric acid solution with a mass concentration of 5wt% is below 1.5Å / s, the thickness of the carbon-doped silicon oxide is 60-150nm, and the thickness ratio of silicon nitride to carbon-doped silicon oxide is 1:(0.5-2).
[0007] In some preferred embodiments of the present invention, the total thickness of the anti-reflection composite layer is 100-250 nm.
[0008] In some preferred embodiments of the present invention, the thickness of silicon nitride is 50-120 nm.
[0009] In some preferred embodiments of the present invention, the refractive index of silicon nitride is 2.0-2.2, and / or the refractive index of carbon-doped silicon oxide is 1.3-1.6.
[0010] In some preferred embodiments of the present invention, the carbon doping concentration of carbon-doped silicon oxide is 1×10 19 cm -3 -9×10 21 cm -3 .
[0011] In some preferred embodiments of the present invention, the carbon doping concentration of the carbon-doped silicon oxide is the same in the thickness direction.
[0012] In some preferred embodiments of the present invention, the carbon doping concentration of the carbon-doped silicon oxide gradually increases in the thickness direction away from the silicon wafer, and the carbon doping concentration ranges from low to high in the range of 1×10 19 cm -3 -9×10 21 cm -3 within the range.
[0013] In some preferred embodiments of the present invention, the carbon doping concentration of the carbon-doped silicon oxide gradually increases to the extent that: in the thickness direction, the absolute value of the difference between adjacent different carbon doping concentrations is within 5×10 19 cm -3 -1×10 21 cm -3 .
[0014] In some preferred embodiments of the present invention, the passivation layer is at least one of amorphous silicon, oxygen-doped amorphous silicon, phosphorus-doped amorphous silicon, silicon oxide and aluminum oxide film layers, and / or the thickness of the passivation layer is 1-10 nm.
[0015] In some preferred embodiments of the present invention, the passivation layer is a combination of silicon oxide and aluminum oxide.
[0016] Further preferably, the thickness ratio of silicon oxide to carbon-doped silicon oxide is 1:(40-150).
[0017] More preferably, the thickness of silicon oxide is 1-2 nm, and the thickness of aluminum oxide is 3-5 nm.
[0018] In some preferred embodiments of the present invention, two ends of the second semiconductor layer extend outward to cover the back side of part of the adjacent first semiconductor layer, and a first semiconductor opening region that does not cover the second semiconductor layer is opened on the back side of the first semiconductor layer, and a second semiconductor opening region is formed between adjacent first semiconductor layers, the second semiconductor opening region is spaced apart from the first semiconductor opening region, and the area between them is a spacer region; in the spacer region, a mask layer is provided between the first semiconductor layer and the second semiconductor layer, or no mask layer is provided; the back contact battery also includes a metal electrode and a conductive film layer laid on the outer surfaces of the first semiconductor layer and the second semiconductor layer, and an isolation groove is provided on the portion of the conductive film layer located in the spacer region; the metal electrode is provided on the outer surfaces of the conductive film layers corresponding to the second semiconductor opening region and the first semiconductor opening region.
[0019] In some preferred embodiments of the present invention, the first semiconductor layer includes a tunneling oxide layer and a first doped polysilicon layer, and the second semiconductor layer includes an intrinsic silicon layer and a second doped silicon layer.
[0020] In a second aspect, the present invention provides a method for preparing a back contact cell having a specific anti-reflection composite layer, comprising the following steps: S1, provide double-sided polished silicon wafers; S2, forming a first semiconductor layer and a mask layer in sequence on the back side of the silicon wafer; S3, performing a first etching opening on the back surface obtained in S2 to form a second semiconductor opening region; S4, forming a velvet surface on the front side of the silicon wafer and the second semiconductor opening region by velvet cleaning; S5. A passivation layer and an anti-reflection composite layer are sequentially arranged on the front side of the silicon wafer, wherein the anti-reflection composite layer comprises silicon nitride and carbon-doped silicon oxide sequentially arranged on the outer surface of the passivation layer, wherein the corrosion rate of the carbon-doped silicon oxide in a hydrofluoric acid solution with a mass concentration of 5wt% is less than 1.5Å / s, the thickness of the carbon-doped silicon oxide is 60-150nm, and the thickness ratio of the silicon nitride to the carbon-doped silicon oxide is 1:(0.5-2); S6, using a laser edge sweeping process to remove the plating layer at the edge of the back side of the silicon wafer; then using a solution etching method to clean the second semiconductor opening area; S7. Depositing a second semiconductor layer on the back side.
[0021] In some preferred embodiments of the present invention, the width of the laser edge scanning in S6 is 0.5-2 cm, and the laser edge scanning time t1 is 5-25 s.
[0022] In some preferred embodiments of the present invention, the laser scanning time t1 in S6 and the coating time t0 used in the preparation of the front carbon-doped silicon oxide and the methane flow rate L introduced therein satisfy the following values in sccm: t1=a×t0+b×L, wherein t1 and t0 are values in s, a and b are coefficients and a is 0.005-0.025, and b is 0.001-0.003.
[0023] In some preferred embodiments of the present invention, the laser etching depth of the laser edge scanning in S6 is 1-10 nm.
[0024] In some preferred embodiments of the present invention, the conditions for laser edge scanning include: the laser used is an ultraviolet picosecond laser or a green light picosecond laser, the pulse width of the laser is less than 5ns, the laser power is 8-20W, the spot is a shaped square spot, the side length of the spot is 100-150μm, and the spot overlap rate is less than 30%.
[0025] In some preferred embodiments of the present invention, the solution etching method in S6 uses a hydrofluoric acid solution, the mass concentration of hydrofluoric acid in the hydrofluoric acid solution is 1%-10%, and the conditions of the solution etching method include: a processing temperature of 20°C-30°C, and a cleaning time of 30-200s.
[0026] In some preferred embodiments of the present invention, silicon nitride and carbon-doped silicon oxide are deposited using PECVD equipment, and the deposition temperature is controlled to be 350-600°C, wherein the conditions for depositing silicon nitride include: introducing silane and ammonia, the flow rate of silane is 800-2000sccm, the flow rate of ammonia is 6000-15000sccm, the deposition pressure is 1300-2500mtorr, and the power is 5kw-20kw; the conditions for depositing carbon-doped silicon oxide include: introducing silane, laughing gas, and methane, the flow rate of silane is 100-1000sccm, the flow rate of laughing gas is 6000-20000sccm, the flow rate of methane is 500-5000sccm, the deposition pressure is 1300-2500mtorr, and the power is 5kw-20kw.
[0027] In some preferred embodiments of the present invention, the method for preparing a back contact cell having a specific anti-reflection composite layer further comprises: S8, performing a second etching opening on a portion of the second semiconductor layer on the back side of the silicon wafer to form a first semiconductor opening region spaced apart from the second semiconductor opening region; S9, depositing a conductive film layer on the back surface obtained in S8; S10, performing a third etching opening on a portion of the conductive film layer located between the first semiconductor opening region and the second semiconductor opening region to form an isolation groove; S11, forming metal electrodes on the outer surfaces of the corresponding conductive film layers in the areas where the first semiconductor opening region and the second semiconductor opening region are located.
[0028] In a third aspect, the present invention provides a back-contact cell, which is prepared by the preparation method of a back-contact cell with a specific anti-reflection composite layer described in the second aspect.
[0029] In a fourth aspect, the present invention provides a photovoltaic module, which includes the back contact cell with the specific anti-reflection composite layer described in the first aspect, or includes the back contact cell described in the third aspect.
[0030] Beneficial effects: The present invention adopts the above-mentioned technical scheme, especially arranges an anti-reflection composite layer including silicon nitride and specific carbon-doped silicon oxide. The corrosion rate of the carbon-doped silicon oxide in a hydrofluoric acid solution with a mass concentration of 5wt% is below 1.5Å / s, and it has strong resistance to chemical solutions (such as acids and alkalis), and can maintain a stable film thickness and anti-reflection effect. In addition, when combined with silicon nitride, it can take into account both passivation performance and optical effects. In combination with controlling the appropriate film thickness ratio of silicon nitride and carbon-doped silicon oxide and the appropriate corrosion rate of carbon-doped silicon oxide, it is beneficial to improve the stability of the film layer and the production yield while taking into account the optical effect, increase the short-circuit current, and improve the battery efficiency.
[0031] During the preparation, when the anti-reflection layer is coated on the front side, there will be a coating layer on the edge of the back side of the silicon wafer and the second semiconductor opening area. If it is not removed, it will affect the conductivity of the first semiconductor area and the passivation effect of the second semiconductor area, affecting the overall production yield. Since carbon-doped silicon oxide has strong corrosion resistance, it can neither be corroded by strong alkali nor by strong acid in the texturing cleaning solution. The coating layer on the back side is difficult to be corroded by the solution. In this regard, in the preparation method of the present invention, a laser edge sweeping process is used in S6 to sweep away the coating layer on the edge of the back side of the silicon wafer to avoid damage to the first semiconductor layer caused by long-term corrosion with the solution. Then, the second semiconductor opening area is cleaned by a solution corrosion method to remove the slight coating layer in the second semiconductor opening area. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0033] Figure 1 It is a schematic structural diagram of a specific embodiment of the back contact battery of the present invention.
[0034] Description of Reference Numerals Silicon wafer 1, tunneling silicon oxide layer 2, N-type doped polysilicon layer 3, passivation layer 5, anti-reflection composite layer 6, silicon nitride 6.1, carbon-doped silicon oxide 6.2, intrinsic hydrogenated amorphous silicon layer 7, P-type doped amorphous silicon layer 8, transparent conductive film layer 9, metal electrode 10. First semiconductor opening area W1, second semiconductor opening area W2, isolation trench W3. DETAILED DESCRIPTION
[0035] In the present invention, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.
[0036] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0037] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Among them, the terms "optional" and "optional" all mean that they may be included or not included (or may be present or not).
[0038] In the present invention, the area close to the silicon wafer is referred to as the inside, and the area far from the silicon wafer is referred to as the outside.
[0039] In a first aspect, the present invention provides a back-contact cell with a specific anti-reflection composite layer, comprising a silicon wafer, a first semiconductor layer and a second semiconductor layer alternately arranged on the back side of the silicon wafer, a passivation layer and an anti-reflection composite layer sequentially arranged on the front side of the silicon wafer, the anti-reflection composite layer comprising silicon nitride and carbon-doped silicon oxide sequentially arranged on the outer surface of the passivation layer, the corrosion rate of the carbon-doped silicon oxide in a hydrofluoric acid solution with a mass concentration of 5wt% is below 1.5Å / s, the thickness of the carbon-doped silicon oxide is 60-150nm, and the thickness ratio of silicon nitride to carbon-doped silicon oxide is 1:(0.5-2).
[0040] The corrosion rate of the carbon-doped silicon oxide in a hydrofluoric acid solution with a mass concentration of 5wt% is below 1.5Å / s, for example, below 1.5Å / s, below 1.3Å / s, below 1.2Å / s, below 1.1Å / s, below 1.0Å / s, below 0.9Å / s, below 0.8Å / s, below 0.7Å / s, below 0.5Å / s, below 0.3Å / s or below 0.2Å / s, preferably below 0.90Å / s.
[0041] The thickness ratio of the silicon nitride to the carbon-doped silicon oxide is 1:(0.5-2), for example, it can be 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1.0, 1:1.2, 1:1.5, 1:1.7 or 1:2 and the range between any two point values, preferably 1:(0.9-2).
[0042] In some preferred embodiments of the present invention, the total thickness of the anti-reflection composite layer is 100-250 nm, for example, 100 nm, 120 nm, 150 nm, 170 nm, 180 nm, 190 nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm or 250 nm and the range between any two point values. Using an anti-reflection composite layer of appropriate thickness is more conducive to reducing the absorption of the front film layer.
[0043] In some preferred embodiments of the present invention, the thickness of silicon nitride is 50-120 nm.
[0044] In some preferred embodiments of the present invention, the refractive index of silicon nitride is 2.0-2.2, and / or the refractive index of carbon-doped silicon oxide is 1.3-1.6. The use of silicon nitride and carbon-doped silicon oxide with appropriate refractive index is more conducive to improving the anti-reflection effect of the combined film layer and increasing the current density of the battery.
[0045] In some preferred embodiments of the present invention, the carbon doping concentration of carbon-doped silicon oxide is 1×10 19 cm -3 -9×10 21 cm -3The use of carbon-doped silicon oxide with an appropriate carbon doping concentration is more conducive to improving the corrosion resistance of carbon-doped silicon oxide.
[0046] In some preferred embodiments of the present invention, the carbon doping concentration of the carbon-doped silicon oxide is the same in the thickness direction.
[0047] In some preferred embodiments of the present invention, the carbon doping concentration of the carbon-doped silicon oxide gradually increases in the thickness direction away from the silicon wafer, and the carbon doping concentration ranges from low to high in the range of 1×10 19 cm -3 -9×10 21 cm -3 The preferred solution of the present invention is more conducive to ensuring the corrosion resistance of carbon-doped silicon oxide while not increasing the optical absorption of the film layer.
[0048] In some preferred embodiments of the present invention, the carbon doping concentration of the carbon-doped silicon oxide gradually increases to the extent that: in the thickness direction, the absolute value of the difference between adjacent different carbon doping concentrations is within 5×10 19 cm -3 -1×10 21 cm -3 , preferably 6×10 19 cm -3 -1×10 21 cm -3 By adopting the preferred solution of the present invention, the carbon doping concentration is increased to an appropriate extent, which is more conducive to adjusting the appropriate refractive index and taking into account both corrosion resistance and optical properties.
[0049] The carbon-doped silicon oxide of the present invention may be gradually increased in a uniform or non-uniform manner, with the former being preferred, as the uniform increase is more conducive to ensuring the stability and uniformity of the coating.
[0050] In some preferred embodiments of the present invention, the passivation layer is at least one of amorphous silicon, oxygen-doped amorphous silicon, phosphorus-doped amorphous silicon, silicon oxide and aluminum oxide film layers.
[0051] Preferably, the thickness of the passivation layer is 1-10 nm.
[0052] In some preferred embodiments of the present invention, the passivation layer is a combination of silicon oxide and aluminum oxide. The use of this preferred solution of the present invention is more conducive to improving the passivation effect of the film layer and the reliability of the product.
[0053] Further preferably, the thickness ratio of silicon oxide to carbon-doped silicon oxide is 1:(40-150), more preferably 1:(60-150), further preferably 1:(80-150), which is more conducive to improving the passivation effect and anti-reflection effect of the film layer.
[0054] More preferably, the thickness of silicon oxide is 1-2 nm, and the thickness of aluminum oxide is 3-5 nm.
[0055] In the present invention, preferably, the first semiconductor layer includes a first passivation layer and a first doped silicon layer, the second semiconductor layer includes a second passivation layer and a second doped silicon layer, and the first passivation layer and the second passivation layer are each independently a tunneling oxide layer or an intrinsic silicon layer. The first doped silicon layer and the second doped silicon layer are each independently polycrystalline silicon, amorphous silicon or microcrystalline silicon. The second doped silicon layer can be doped amorphous silicon or microcrystalline silicon. The intrinsic silicon layer is preferably an intrinsic amorphous silicon layer (such as an intrinsic hydrogenated amorphous silicon layer). One of the first doped polycrystalline silicon layer and the second doped silicon layer is N-type and the other is P-type.
[0056] In some preferred embodiments of the present invention, the first semiconductor layer includes a tunneling oxide layer and a first doped polysilicon layer, and the second semiconductor layer includes an intrinsic silicon layer and a second doped silicon layer. The combined passivation structure, combined with the specific passivation layer and anti-reflection recombination layer of the present invention, is more conducive to improving the conversion efficiency of the battery.
[0057] Further preferably, the thickness and corresponding doping concentration of the tunnel oxide layer or intrinsic silicon layer, the first doped polysilicon layer and the second doped silicon layer of the present invention can refer to the range of the prior art respectively, and can be used in the present invention. For example, the thickness of the tunnel oxide layer is 1-2nm, the thickness of the intrinsic silicon layer is 5-15nm; the thickness of the second doped silicon layer is 7-45nm, and the effective doping concentration is 2×10 18 cm -3 -3×10 20 cm -3 The thickness of the first doped polysilicon layer is 80-150 nm, and the effective doping concentration is greater than 5×10 18 cm -3 .
[0058] In some preferred embodiments of the present invention, both ends of the second semiconductor layer extend outward to cover part of the back side of the adjacent first semiconductor layer, and a first semiconductor opening region that does not cover the second semiconductor layer is opened on the back side of the first semiconductor layer, and a second semiconductor opening region is formed between adjacent first semiconductor layers. The second semiconductor opening region is spaced apart from the first semiconductor opening region, and the area between them is a spacing region.
[0059] Preferably, in the spacer, a mask layer is disposed between the first semiconductor layer and the second semiconductor layer, or no mask layer is disposed. The type and thickness of the mask layer can refer to the prior art. For example, the mask layer can be at least one of silicon nitride, silicon oxide, silicon oxynitride, or nitrogen-containing polysilicon, and the thickness of the mask layer is 50-100 nm.
[0060] Preferably, in the present invention, the back-contact battery also includes a metal electrode and a conductive film layer laid on the outer surfaces of the first semiconductor layer and the second semiconductor layer, and an isolation groove is provided on the portion of the conductive film layer located in the spacing area; the metal electrode is arranged on the outer surfaces of the conductive film layers corresponding to the second semiconductor opening area and the first semiconductor opening area.
[0061] Preferably, in the present invention, a portion of the silicon wafer located at the position of the second semiconductor opening region is a textured surface, and a portion of the silicon wafer at a position corresponding to the first semiconductor layer is a polished surface.
[0062] In a second aspect, the present invention provides a method for preparing a back contact cell having a specific anti-reflection composite layer, comprising the following steps: S1, provide double-sided polished silicon wafers; S2, forming a first semiconductor layer and a mask layer in sequence on the back side of the silicon wafer; S3, performing a first etching opening on the back surface obtained in S2 to form a second semiconductor opening region; S4, forming a velvet surface on the front side of the silicon wafer and the second semiconductor opening region by velvet cleaning; S5. A passivation layer and an anti-reflection composite layer are sequentially arranged on the front side of the silicon wafer, wherein the anti-reflection composite layer comprises silicon nitride and carbon-doped silicon oxide sequentially arranged on the outer surface of the passivation layer, wherein the corrosion rate of the carbon-doped silicon oxide in a hydrofluoric acid solution with a mass concentration of 5wt% is less than 1.5Å / s, the thickness of the carbon-doped silicon oxide is 60-150nm, and the thickness ratio of the silicon nitride to the carbon-doped silicon oxide is 1:(0.5-2); S6, using a laser edge sweeping process to remove the plating layer at the edge of the back side of the silicon wafer; then using a solution etching method to clean the second semiconductor opening area; S7. Depositing a second semiconductor layer on the back side.
[0063] The texturing cleaning in S4 of the present invention can refer to the corresponding process in the prior art. For example, the texturing solution used is a mixture of alkali (such as potassium hydroxide or sodium hydroxide), texturing additives and water, wherein the mass percentage of the alkali is 1%-5%, and the mass percentage of the texturing additive is 0.5%-1%. Further, the texturing conditions may include: the texturing time is 8-30min, and the texturing temperature is 75℃-85℃. The texturing additives can be obtained commercially. The final cleaning conditions in the texturing cleaning can be adjusted according to whether the mask layer needs to be removed. For example, when the mask layer needs to be removed, the final cleaning conditions include: the cleaning solution used for the final cleaning is an acid solution such as HF, the mass percentage of HF in the HF acid solution is 0.5%-5%, the mass percentage of deionized water contained is 95%-99.5%, the processing temperature is 20℃-30℃, and the removal time is 60-500s.
[0064] In the present invention, it can be understood that the wrap plating is mainly carried out from the front side to the edges around the back side of the silicon wafer. S6 adopts a laser edge scanning process to remove the wrap plating layer at the edge of the back side of the silicon wafer, while the slight wrap plating layer in most of the middle area of the back side including the second semiconductor opening area can be removed by solution etching.
[0065] In some preferred embodiments of the present invention, the width of the laser edge sweep in S6 is 0.5-2 cm, and the laser edge sweep time t1 is 5-25 s. The laser edge sweep time refers to the total time for the laser to remove all the surrounding coatings on the edge of a silicon wafer. Using an appropriate laser edge sweep width and time is more conducive to removing the surrounding coatings while reducing damage to the first semiconductor layer.
[0066] In some preferred embodiments of the present invention, the laser edge sweeping time t1 in S6 and the coating time t0 used in the preparation of the front carbon-doped silicon oxide and the methane flow rate L passed therein in sccm satisfy: t1=a×t0+b×L, wherein t1 and t0 are values in s, a and b are coefficients and a is 0.005-0.025, and b is 0.001-0.003. In the present invention, it is preferred to determine the laser edge sweeping time t1 based on the coating time t0 of the front carbon-doped silicon oxide and the methane flow rate L passed therein, so that the coating layer can be removed more thoroughly, which is more conducive to improving the conversion efficiency of the battery.
[0067] In some preferred embodiments of the present invention, the laser etching depth of the laser edge scanning in S6 is 1-10 nm, which is more conducive to reducing the damage of the laser to the first semiconductor layer.
[0068] In some preferred embodiments of the present invention, the laser edge scanning conditions include: the laser used is an ultraviolet picosecond laser or a green light picosecond laser, the laser pulse width is less than 5ns, and the laser power is 8-20 W. The use of this preferred laser edge scanning condition is more conducive to reducing the damage of the laser to the back film layer.
[0069] Preferably, the laser edge sweeping condition also includes: the light spot is a shaped square light spot, the side length of the light spot is 100-150 μm, and the light spot overlap rate is less than 30%. The solution of the preferred laser edge sweeping condition is more conducive to reducing laser etching damage.
[0070] In some preferred embodiments of the present invention, the solution corrosion method in S6 uses a hydrofluoric acid solution, and the mass concentration of hydrofluoric acid in the hydrofluoric acid solution is 1%-10%.
[0071] Preferably, the conditions of the solution etching method include: a processing temperature of 20° C.-30° C., and a cleaning time of 30-200 s.
[0072] In some preferred embodiments of the present invention, silicon nitride and carbon-doped silicon oxide are deposited using PECVD equipment, and the deposition temperature is controlled to be 350-600°C.
[0073] Preferably, in the present invention, the conditions for depositing silicon nitride include: introducing silane and ammonia, the flow rate of silane is 800-2000sccm, the flow rate of ammonia is 6000-15000sccm, the deposition pressure is 1300-2500mtorr, and the power is 5kw-20kw.
[0074] Preferably, the conditions for depositing carbon-doped silicon oxide include: introducing silane, nitrous oxide and methane, the flow rate of silane is 100-1000sccm, the flow rate of nitrous oxide is 6000-20000sccm, the flow rate of methane is 500-5000sccm, the deposition pressure is 1300-2500mtorr, and the power is 5kw-20kw.
[0075] Preferably, in the present invention, the texturing cleaning process in S4 further includes the step of selecting whether to perform cleaning to remove the mask layer outside the second semiconductor opening region on the back side of the silicon wafer as required.
[0076] In some preferred embodiments of the present invention, the method for preparing a back contact cell having a specific anti-reflection composite layer further comprises: S8, performing a second etching opening on a portion of the second semiconductor layer on the back side of the silicon wafer to form a first semiconductor opening region spaced apart from the second semiconductor opening region; S9, depositing a conductive film layer on the back surface obtained in S8; S10, performing a third etching opening on a portion of the conductive film layer located between the first semiconductor opening region and the second semiconductor opening region to form an isolation groove; S11, forming metal electrodes on the outer surfaces of the corresponding conductive film layers in the areas where the first semiconductor opening region and the second semiconductor opening region are located.
[0077] In a third aspect, the present invention provides a back contact cell, which is prepared by the preparation method of the back contact cell with a specific anti-reflection composite layer described in the second aspect. The back contact cell has the same structure and performance as the back contact cell of the first aspect, and will not be described in detail here.
[0078] In a fourth aspect, the present invention provides a photovoltaic module, which includes the back contact cell with the specific anti-reflection composite layer described in the first aspect, or includes the back contact cell described in the third aspect.
[0079] The embodiments of the present invention are described in detail below, which are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0080] Example 1 A back contact battery, such as Figure 1 As shown, it is prepared by the following steps: S1, silicon wafer 1 (N-type single crystal silicon wafer) double-sided polishing: S2, forming a first semiconductor layer and a mask layer on the back side of the silicon wafer 1: The first semiconductor layer includes a tunneling silicon oxide layer 2 and an N-type doped polysilicon layer 3. The thickness of the tunneling silicon oxide layer 2 is 1.5 nm, the thickness of the N-type doped polysilicon layer 3 is 120 nm, and the effective doping concentration is 2.5×10 20 cm -3 The mask layer is silicon nitride and has a thickness of 80 nm.
[0081] S3, etching an opening on the back side of the silicon wafer 1 for the first time to form a second semiconductor opening region W2; S4, performing texturing and cleaning on the second semiconductor opening area W2 on the front and back sides of the silicon wafer 1; The texturing liquid used for texturing cleaning is a mixture of potassium hydroxide, texturing additive (commercially available) and water, wherein the mass percentage of potassium hydroxide is 2%, and the mass percentage of texturing additive is 0.5%. The texturing time is 10 minutes, and the texturing temperature is 80°C.
[0082] During the texturing process on the front side, the silicon nitride mask layer on the back side of the silicon wafer is also removed by the final cleaning solution. The solution used to remove the mask layer is HF acid solution, the HF mass percentage is 0.5%, the processing temperature is 25°C, and the removal time is 200s. S5, forming a passivation layer 5 and an anti-reflection composite layer 6 on the front side of the silicon wafer 1: The passivation layer 5 is a combination of silicon oxide and aluminum oxide formed in sequence, the thickness of the silicon oxide is 1 nm, and the thickness of the aluminum oxide is 5 nm; The anti-reflection composite layer 6 is a combination of silicon nitride 6.1 and carbon-doped silicon oxide 6.2 formed in sequence, and is deposited by PECVD equipment at a deposition temperature of 450° C. When depositing silicon nitride 6.1, the flow rate of silane is 1000 sccm, the flow rate of ammonia is 9500 sccm, the deposition pressure is 1700 mtorr, and the power is 10 kW; When depositing carbon-doped silicon oxide 6.2, the flow rate of silane is 300sccm, the flow rate of nitrous oxide is 10000sccm, the flow rate of methane is 1000sccm, the deposition pressure is 1600mtorr, and the power is 10kW; the carbon doping concentration of carbon-doped silicon oxide is the same in the thickness direction and the carbon doping concentration is 8.5×10 19 cm -3 .
[0083] The total thickness of the anti-reflection composite layer 6 is 200nm, of which the thickness of silicon nitride 6.1 is 90nm and the refractive index is 2.03; the thickness of carbon-doped silicon oxide 6.2 is 110nm and the refractive index is 1.48, and the corrosion rate of carbon-doped silicon oxide 6.2 in a hydrofluoric acid solution with a mass concentration of 5wt% is 0.6Å / s. According to calculations, the thickness ratio of silicon nitride 6.1 and carbon-doped silicon oxide 6.2 is 1:1.2. The thickness ratio of silicon oxide to carbon-doped silicon oxide 6.2 is 1:110.
[0084] S6, removing the back side coating and cleaning the second semiconductor opening area W2: First, laser edge scanning is used to remove the coating layer within 1.5 cm from the edge of the back of the silicon wafer. The type of laser used for laser edge scanning is ultraviolet picosecond laser, with a pulse width of 2ns, a laser power of 10W, a laser edge scanning width of 1.5cm, a laser etching depth of 3nm, and a shaped square spot with a side length of 150μm, an overlap rate of 15%, and a laser edge scanning time t1 of 8s. Laser edge scanning time t1 and front carbon-doped silicon oxide coating time t0 And the value of the methane flow rate L (in sccm) is in a certain positive relationship: t1=0.015t0+0.002L, where the units of t1 and t0 are s.
[0085] Then, HF acid solution is used for further cleaning, wherein the mass percentage of HF is 2%, the mass percentage of deionized water is the balance, the treatment temperature is 25° C., and the cleaning time is 100 s; S7, forming a second semiconductor layer on the back side of the silicon wafer 1; The second semiconductor layer is a stack of an intrinsic hydrogenated amorphous silicon layer 7 and a P-type doped amorphous silicon layer 8; the thickness of the intrinsic hydrogenated amorphous silicon layer 7 is 10 nm, the thickness of the P-type doped amorphous silicon layer 8 is 15 nm, and the effective doping concentration is 5.6×10 19 cm -3 ; S8, etching an opening on the back side of the silicon wafer 1 for the second time to form a first semiconductor opening region W1; S9, depositing a transparent conductive film layer 9 on the back side of the silicon wafer 1; S10, etching an opening on the back side of the silicon wafer 1 for the third time to form an isolation trench W3; after etching, the resistance between the first semiconductor and the second semiconductor is greater than 1 kΩ.
[0086] S11 , forming metal electrodes 10 at the outer surfaces of the first semiconductor opening region W1 and the second semiconductor opening region W2 corresponding to the back side of the silicon wafer.
[0087] Example 2 The method is carried out with reference to Example 1, except that the thickness of the carbon-doped silicon oxide is adjusted to satisfy the thickness ratio of silicon nitride to carbon-doped silicon oxide of 1:0.8.
[0088] Example 3 The method is carried out in accordance with Example 1, except that the carbon doping concentration of carbon-doped silicon oxide is adjusted to 4.5×10 19 cm -3 The process that needs to be adjusted to meet this condition is to reduce the flow rate of methane by 40%. According to the test, the corrosion rate of carbon-doped silicon oxide in a hydrofluoric acid solution with a mass concentration of 5wt% is 0.95Å / s, and the refractive index of carbon-doped silicon oxide is 1.5.
[0089] Example 4 The method is carried out in accordance with Example 1, except that the carbon doping concentration of the carbon-doped silicon oxide is gradually increased in the thickness direction away from the silicon wafer, and the carbon doping concentration is 1×10 19 cm -3 -9×10 21 cm -3 , the amplitude of the uniform and gradual increase satisfies: in the thickness direction, the absolute value of the difference between adjacent different carbon doping concentrations is 8×10 19 cm -3 The process that needs to be adjusted to meet this condition is to gradually increase the methane flow rate to the target carbon doping concentration for each layer. According to the test, the corrosion rate of carbon-doped silicon oxide in a hydrofluoric acid solution with a mass concentration of 5wt% is 0.56Å / s, and the refractive index of carbon-doped silicon oxide is 1.45.
[0090] Example 5 The method is carried out in accordance with Example 4, except that the carbon doping concentration of the carbon-doped silicon oxide is adjusted to increase uniformly at different rates. Specifically, the carbon doping concentration of the first layer is 5×10 19 cm -3 The carbon doping concentration of the last layer remains unchanged, which is 9×10 21 cm -3 , the amplitude of the uniform and gradual increase satisfies: in the thickness direction, the absolute value of the difference between adjacent different carbon doping concentrations is 5×10 19 cm -3 The process that needs to be adjusted to meet this condition is to increase the methane flow rate by a corresponding multiple for each layer to the target carbon doping concentration. According to the test, the corrosion rate of carbon-doped silicon oxide in a hydrofluoric acid solution with a mass concentration of 5wt% is 0.31Å / s, and the refractive index of carbon-doped silicon oxide is 1.32.
[0091] Example 6 The method is carried out with reference to Example 1, except that the thickness of silicon oxide in the passivation layer is adjusted to be a combination of silicon oxide and aluminum oxide to be 2 nm, so that the thickness ratio of silicon oxide to carbon-doped silicon oxide is 1:55.
[0092] Comparative Example 1 The process is carried out with reference to Example 1, except that the anti-reflection layer is silicon nitride, and carbon-doped silicon oxide is not provided.
[0093] Comparative Example 2 The method is carried out in accordance with Example 1, except that the carbon-doped silicon oxide in the anti-reflection layer is replaced by silicon oxide, that is, no carbon is doped, and the etching rate of silicon oxide in a hydrofluoric acid solution with a mass concentration of 5 wt% is 15 Å / s.
[0094] Comparative Example 3 The process is carried out with reference to Example 1, except that the anti-reflection layer is carbon-doped silicon oxide, and silicon nitride is not provided.
[0095] Comparative Example 4 The method is carried out with reference to Example 1, except that the thickness of the carbon-doped silicon oxide is adjusted to satisfy the thickness ratio of silicon nitride to carbon-doped silicon oxide of 1:0.3.
[0096] Test Case The back contact cells obtained in the above-mentioned embodiments and comparative examples were subjected to performance tests, and the results are shown in Table 1, wherein the performance indicators of each embodiment and comparative example were converted using embodiment 1 as a reference benchmark, the data of embodiment 1 was normalized to 1.000, and other examples were converted based on embodiment 1, such as the reflectivity of comparative example 1 / the reflectivity of embodiment 1 was 1.615. The optical effect index refers to the reflectivity, which is obtained by testing with an ultraviolet spectrophotometer. The film stability index refers to the retention of the thickness of the anti-reflection layer, specifically the ratio of (the thickness of the anti-reflection layer before passing through a hydrofluoric acid solution with a mass concentration of 5wt% - the thickness of the anti-reflection layer after passing through a hydrofluoric acid solution with a mass concentration of 5wt%) / the thickness of the anti-reflection layer before passing through a hydrofluoric acid solution with a mass concentration of 5wt%, which is obtained by testing the film thickness with an ellipsometer. The production yield refers to the proportion of qualified batteries in the production of a batch (100 batteries).
[0097] Table 1
[0098] It can be seen from the above results that, compared with the comparative example, the embodiment scheme of the present invention is beneficial to taking into account the optical effect of reducing the reflectivity while improving the stability of the film layer and the production yield, increasing the short-circuit current, and improving the battery efficiency.
[0099] Furthermore, according to Example 1 and Examples 2-6, it can be seen that the adoption of the preferred solution of the present invention is more conducive to increasing the short-circuit current, improving the battery efficiency and the production yield.
[0100] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A back contact cell with a specific anti-reflection composite layer, comprising a silicon wafer, a first semiconductor layer and a second semiconductor layer alternately arranged on the back of the silicon wafer, and a passivation layer and an anti-reflection composite layer sequentially arranged on the front of the silicon wafer, characterized in that: The anti-reflection composite layer includes silicon nitride and carbon-doped silicon oxide sequentially arranged on the outer surface of the passivation layer. The corrosion rate of the carbon-doped silicon oxide in a hydrofluoric acid solution with a mass concentration of 5wt% is below 1.5Å / s, the thickness of the carbon-doped silicon oxide is 60-150nm, and the thickness ratio of silicon nitride to carbon-doped silicon oxide is 1:(0.5-2).
2. The back contact cell with a specific anti-reflection composite layer according to claim 1, characterized in that: The total thickness of the anti-reflection composite layer is 100-250 nm, and / or the thickness of the silicon nitride is 50-120 nm.
3. The back contact cell with a specific anti-reflection composite layer according to claim 1, characterized in that: The refractive index of silicon nitride is 2.0-2.2, and / or the refractive index of carbon-doped silicon oxide is 1.3-1.
6.
4. The back contact cell with a specific anti-reflection composite layer according to claim 1, characterized in that: The carbon doping concentration of carbon-doped silicon oxide is 1×10 19 cm -3 -9×10 21 cm -3 .
5. The back contact cell with a specific anti-reflection composite layer according to claim 1 or 4, characterized in that: The carbon doping concentration of the carbon-doped silicon oxide is uniform in the thickness direction.
6. The back contact cell with a specific anti-reflection composite layer according to claim 1 or 4, characterized in that: The carbon doping concentration of carbon-doped silicon oxide gradually increases in the thickness direction away from the silicon wafer, and its carbon doping concentration ranges from low to high. 19 cm -3 -9×10 21 cm -3 within the range.
7. The back contact cell with a specific anti-reflection composite layer according to claim 6, characterized in that: The carbon doping concentration of carbon-doped silicon oxide gradually increases to the extent that: in the thickness direction, the absolute value of the difference between adjacent different carbon doping concentrations is within 5×10 19 cm -3 -1×10 21 cm -3 .
8. The back contact cell with a specific anti-reflection composite layer according to claim 1, characterized in that: The passivation layer is at least one of amorphous silicon, oxygen-doped amorphous silicon, phosphorus-doped amorphous silicon, silicon oxide and aluminum oxide film layers, and / or the thickness of the passivation layer is 1-10 nm.
9. The back contact cell with a specific anti-reflection composite layer according to claim 1, characterized in that: The passivation layer is a combination of silicon oxide and aluminum oxide, wherein: The thickness ratio of silicon oxide to carbon-doped silicon oxide is 1:(40-150); and / or, The thickness of silicon oxide is 1-2 nm, and the thickness of aluminum oxide is 3-5 nm.
10. The back contact cell with a specific anti-reflection composite layer according to claim 1, characterized in that: The two ends of the second semiconductor layer extend outward to cover the back side of the adjacent first semiconductor layer, and a first semiconductor opening region that does not cover the second semiconductor layer is opened on the back side of the first semiconductor layer, and a second semiconductor opening region is formed between the adjacent first semiconductor layers, and the second semiconductor opening region is arranged at intervals from the first semiconductor opening region, and the area between them is a spacing region; in the spacing region, a mask layer is provided between the first semiconductor layer and the second semiconductor layer, or no mask layer is provided; the back contact battery also includes a metal electrode and a conductive film layer laid on the outer surfaces of the first semiconductor layer and the second semiconductor layer, and an isolation groove is provided on the portion of the conductive film layer located in the spacing region; the metal electrode is provided on the outer surfaces of the conductive film layers corresponding to the second semiconductor opening region and the first semiconductor opening region; and / or, The first semiconductor layer includes a tunneling oxide layer and a first doped polysilicon layer, and the second semiconductor layer includes an intrinsic silicon layer and a second doped silicon layer.
11. A method for preparing a back contact cell having a specific anti-reflection composite layer, characterized in that: The steps include: S1, provide double-sided polished silicon wafers; S2, forming a first semiconductor layer and a mask layer in sequence on the back side of the silicon wafer; S3, performing a first etching opening on the back surface obtained in S2 to form a second semiconductor opening region; S4, forming a velvet surface on the front side of the silicon wafer and the second semiconductor opening region by velvet cleaning; S5. A passivation layer and an anti-reflection composite layer are sequentially arranged on the front side of the silicon wafer, wherein the anti-reflection composite layer comprises silicon nitride and carbon-doped silicon oxide sequentially arranged on the outer surface of the passivation layer, wherein the corrosion rate of the carbon-doped silicon oxide in a hydrofluoric acid solution with a mass concentration of 5wt% is less than 1.5Å / s, the thickness of the carbon-doped silicon oxide is 60-150nm, and the thickness ratio of the silicon nitride to the carbon-doped silicon oxide is 1:(0.5-2); S6, using a laser edge sweeping process to remove the plating layer at the edge of the back side of the silicon wafer; then using a solution etching method to clean the second semiconductor opening area; S7. Depositing a second semiconductor layer on the back side.
12. The method for preparing a back contact cell with a specific anti-reflection composite layer according to claim 11, characterized in that: The width of the laser edge scanning in S6 is 0.5-2 cm, and the laser edge scanning time t1 is 5-25 s; and / or, The laser scanning time t1 in S6, the coating time t0 used in the preparation of the front carbon-doped silicon oxide, and the methane flow rate L introduced in the unit of sccm satisfy: t1=a×t0+b×L, where t1 and t0 are values in units of s, a and b are coefficients and a is 0.005-0.025, and b is 0.001-0.
003.
13. The method for preparing a back contact cell having a specific anti-reflection composite layer according to claim 11 or 12, characterized in that: The laser etching depth of the laser edge scanning in S6 is 1-10 nm; and / or, The conditions for laser edge scanning include: the laser used is an ultraviolet picosecond laser or a green light picosecond laser, the laser pulse width is less than 5ns, the laser power is 8-20W, the light spot is a shaped square spot, the side length of the light spot is 100-150μm, and the spot overlap rate is less than 30%.
14. The method for preparing a back contact cell having a specific anti-reflection composite layer according to claim 11, characterized in that: The solution corrosion method in S6 uses a hydrofluoric acid solution, the mass concentration of hydrofluoric acid in the hydrofluoric acid solution is 1%-10%, and the conditions of the solution corrosion method include: a processing temperature of 20℃-30℃, and a cleaning time of 30-200s; and / or, Silicon nitride and carbon-doped silicon oxide are deposited by PECVD equipment, and the deposition temperature is controlled to be 350-600°C. The conditions for depositing silicon nitride include: introducing silane and ammonia, the silane flow rate is 800-2000sccm, the ammonia flow rate is 6000-15000sccm, the deposition pressure is 1300-2500mtorr, and the power is 5kw-20kw; the conditions for depositing carbon-doped silicon oxide include: introducing silane, laughing gas, and methane, the silane flow rate is 100-1000sccm, the laughing gas flow rate is 6000-20000sccm, the methane flow rate is 500-5000sccm, the deposition pressure is 1300-2500mtorr, and the power is 5kw-20kw.
15. The method for preparing a back contact cell having a specific anti-reflection composite layer according to claim 11, characterized in that: The method for preparing the back contact cell having the specific anti-reflection composite layer also includes: S8, performing a second etching opening on a portion of the second semiconductor layer on the back side of the silicon wafer to form a first semiconductor opening region spaced apart from the second semiconductor opening region; S9, depositing a conductive film layer on the back surface obtained in S8; S10, performing a third etching opening on a portion of the conductive film layer located between the first semiconductor opening region and the second semiconductor opening region to form an isolation groove; S11, forming metal electrodes on the outer surfaces of the corresponding conductive film layers in the areas where the first semiconductor opening region and the second semiconductor opening region are located.
16. A back contact battery, characterized in that: The battery is prepared by the method for preparing a back contact battery with a specific anti-reflection composite layer as described in any one of claims 11 to 15.
17. A photovoltaic module, characterized in that: It comprises a back contact cell having a specific anti-reflection composite layer as claimed in any one of claims 1 to 10, or comprises a back contact cell as claimed in claim 16.
Citation Information
Patent Citations
High-selectivity carbon-doped Poly etching solution and preparation and etching methods thereof
CN117866636A
TOPCon solar cell and preparation method and application thereof
CN117995916A
Back contact heterojunction solar cell, preparation method thereof and cell module
CN118825103A
Back contact battery and preparation method thereof
CN118825137A
Selective deposition of silicon dielectric film
US20240170283A1
Cited By
Back contact battery with specific emitter and preparation method and application thereof
CN120152391A
Back-contact battery with a specific emitter, preparation method and application thereof
CN120152391B